Tumors With Neuroectodermal Differentiation of the Uterus and Ovary: A Series of 12 Cases and Review of the Literature. (11th September 2019) - Ge, Li; Zhou, Amy; Maksem, John; Gennette, Sarah; Schimp, Veronica
Abstract: Objectives: Primitive neuroectodermal tumors (PNETs) are a group of small round cell tumors most commonly found in the central nervous system, soft tissue, or bone. Such tumors arising in the uterus or ovary are rare. In this study, we describe the clinicopathologic features from a series of gynecological tumors with neuroectodermal differentiation. Methods: In a retrospective review, 5 years of departmental archives were searched for gynecological tumors diagnosed at Orlando Health's Department of Pathology. Clinicopathological information was analyzed, including age at diagnosis, tumor size, depth of invasion, other component, pathologic stage, FIGO stage, immunohistochemical stains, months of follow-up, and current disease status. Results: Twelve fully staged tumors with neuroectodermal differentiation were identified. Eleven were of uterine origin and one was of ovarian origin. Ages at diagnosis ranged from 38 to 78 years (median 65). Neuroectodermal component was variable in morphology, including lymphocyte-like small cells in sheets, perivascular pseudorosettes, or cords; larger cells with prominent nucleoli with or without cystic change; and giant cells resembling megakaryocytes. Components other than neuroectodermal differentiation included carcinosarcoma, dedifferentiated endometrioid carcinoma, and high-grade serous carcinoma. Membranous and/or paranuclear dot-like CD99 immunoreactivity were in all cases. Ten patients were deceased due to disease at 1 to 33 months follow-up, while one patient was alive without evidence of disease after 61 months follow-up, possibly due to being able to tolerate a different therapeutic protocol for peripheral PNET. Conclusion: Neuroectodermal differentiation may be found as components of other gynecological tumors, especially those with an aggressive phenotype and high-stage disease. The neuroectodermal component comprises a spectrum of cytohistological features. Because of its presentation in the shadow of other components, it may be more common than is generally assumed. Mortality remains high, but recognition of neuroectodermal differentiation in gynecologic tumors might introduce a different therapeutic approach and potentially improve clinical outcomes.